Analisis Kemampuan Komunikasi Matematis Siswa Ditinjau dari Hasil Belajar pada Materi Persamaan Linear Satu Variabel - Fitria Febriani Putri; Muhammad Turmuzi; Junaidi Junaidi; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine students’ mathematical communication skills in terms of learning outcomes in the one-variable linear equation material. The resreach method used in description test and interview. The subjects in this study wrw 26 students. This type of resreach is descriptive qualitative resreach. Based on data analysis 1) students with an average score of 90 have high mathematical communication skills, 2) students with an average score of 89,8 have moderate mathematical communication skills and 3) students with an average score of 83,5 have low mathematical communication skills.